Aspek Hukum Wanprestasi Pemadaman Listrik Oleh PT Perusahaan Listrik Negara Terhadap Perusahaan Atas Perjanjian Kerja Jual Beli Tenaga Listrik Dan Perlindungan Hukum Terhadap Perusahaan Selaku Konsumen - Rizkya Nur Azizah; Rahmi Zubaedah (Peneliti.net, 2023)
This study aims to determine the factors that cause power outages, the legal consequences of default by PT PLN and how efforts to realize the implementation of legal protection. The problem is what factors lead to defaults of power outages by PT Perusahaan Listrik Negara against companies for power sale and purchase agreements, what are the legal consequences of defaults for power outages by PT Perusahaan Listrik Negara against companies for power sale and purchase agreements, what efforts can be made? carried out by the company as a consumer to realize the implementation of the legal protection of default on power outages by PT Perusahaan Listrik Negara against the company for the work agreement of buying and selling electricity.In this study the authors used normative juridical research methods, the nature of this research used descriptive analytical research methods. The types of data in this study are primary and secondary data. Collecting data in this study with literature study and interviews. Data analysis techniques in this study used qualitative analysis which included data collection, data presentation, and drawing conclusions.The results of this study indicate that the factor causing the default of the blackout by PT Perusahaan Listrik Negara against the company for the work and purchase agreement of electricity is the maintenance of the network of PT. PLN (Persero) for transformers, cables and other supporting equipment must receive regular maintenance. The legal consequence of the default power outage by PT Perusahaan Listrik Negara against the company for the electricity sale and purchase agreement is the existence of material losses and damage to production machines due to blackouts. As well as the efforts made by the company as a consumer to realize the implementation of the legal protection of default on power outages by PT Perusahaan Listrik Negara against the company for the electricity purchase and sale agreement is to take legal action by negotiating with PT PLN through the medium of letters, which in the letter stated that the request for compensation refers to Regulation of the Minister of Energy and Mineral Resources No. 27 of 2017 which aims to obtain compensation (compensation) with the existing provisions in Regulation of the Minister of Energy and Mineral Resources No. 27 of 2017.